Needs Analysis of College Students for ESP Under the Scope “New Liberal Arts” - Bian, Yuzhu; Mala Bt Ibrahim, Noor (International Journal of English Language Education, 2024)
The term “new liberal arts” encourages integrating traditional liberal arts with other disciplines to promote the efficacy of education. It has been well received all around China, especially in higher education. Under such a background, ESP courses must be tailored to equip college students with sufficient knowledge and training that integrates English with professional expertise. The researchers designed a questionnaire to collect data from five perspectives to better gain insight into students’ needs for ESP courses. The central part of the questionnaire adopted 32 items of the Likert scale and one open-ended question, focusing on the evaluation of ESP courses, assessment of students’ current English ability, students’ needs for ESP courses, and what are the main problems hindering current ESP teaching for students and teachers. The questionnaire was distributed to the participants on an online survey platform. The participants were junior or senior undergraduates and ESP teachers from twelve public universities in China. After the survey, the researchers collected 1078 questionnaires for students and 213 for teachers. The results showed that students and teachers did not think positively of current ESP courses and students’ current English ability, and students had the need for ESP courses on different scales. Furthermore, the study also found that there were discrepancies between the students and teachers with regard to specific items. The findings suggest that an interdisciplinary perspective is needed when carrying out ESP courses, and consensus-based collaboration between students and teachers is also indispensable.